On the optimality of privacy in sequential contracting - Giacomo Calzolari; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
This paper considers an environment where two principals sequentially contract with a common agent and studies the exchange of information between the two bilateral relationships. We show that when (a) the upstream principal is not personally interested in the decisions taken by the downstream principal, (b) the agent's exogenous private information has a vertical structure in the sense that the sign of the single crossing condition is the same for upstream and downstream decisions, and (c) preferences in the downstream relationship are separable, then the upstream principal optimally commits to full privacy, whatever price the downstream principal is willing to pay to receive information. On the contrary, when any of the above conditions is violated, the upstream principal may find it strictly optimal to disclose a (noisy) signal of the agent's exogenous type and/or the result of his upstream contractual activity, even if she can not make the downstream principal pay for the information she receives. We also show that disclosure does not necessarily reduce the equilibrium payoff of the agent and may lead to a Pareto improvement for the three players.
Keywords: D82; C73; L1; 330; contractual and informational externalities; mechanism design; optimal disclosure policy; sequential common agency; exogenous and endogenous private information; Extensives Spiel; Vertragstheorie; Agency Theory; Asymmetrische Information; Theorie